INDUSTRI KREATIF PELEPAH PISANG DI DESA AMBENGAN, KECAMATAN SUKASADA, KABUPATEN BULELENG - Mutria Farhaeni (STIE BIITM, 2018)
The purpose of this research is to know the creative industry of banana tree in Ambengan Village, Sukasada District, Buleleng Regency. Banana plantations in the village of Ambengan very easy to find. Ambengan village community has innovation and creative and creative by exploiting the potential of its territory, namely banana stem as handicrafts. This research was conducted by survey and observation method in field to banana banana craftsman community. The method used is purposive sampling that is by determining the key informant then proceed with snowball method with the intention to get data and information as much as possible from other informant. The tool used is in the form of interviews. From the interviews with key informants and other informants then studied and narrated in the form of descriptive. From the results of the study can be concluded first, with the existence of banana banana industry benefits for the community, among others, for business owners are able to increase family income and increase creativity in the field of art, while the challenge faced is the difficulty of getting raw materials during the rainy season. Secondly, there is no clear separation of business and household financial management, related to sales management problem where craftsmen do not ask for down payment (DP) to the buyer, in the case of marketing, craftsmen do not have website / e-commerce as media of promotion / online stores of products they produce, whereas in today's modern era of marketing is quite effective form is by utilizing information and communication technology (ICT). Third, the innovation of the resulting product by combining it with sand and air brush.